Fruit Morphology, Citrulline, and Arginine Levels in Diverse Watermelon (Citrullus lanatus) Germplasm Collections - Awraris Derbie Assefa; On-Sook Hur; Na-Young Ro; Jae-Eun Lee; Ae-Jin Hwang; Bich-Saem Kim; Ju-Hee Rhee; Jung-Yoon Yi; Ji-Hyun Kim; Ho-Sun Lee; Jung-Sook Sung; Myung-Kon Kim; et al. (Plants, 2020)
Watermelon (Citrullus lanatus) is a non-seasonal, economically important, cucurbit cultivated throughout the world, with Asia as a continent contributing the most. As part of the effort to diversify watermelon genetic resources in the already cultivated group, this study was devoted to providing baseline data on morphological quality traits and health-beneficial phytonutrients of watermelon germplasm collections, thereby promoting watermelon research and cultivation programs. To this end, we reported morphological traits, citrulline, and arginine levels of watermelon genetic resources obtained from the gene bank of Agrobiodiversity Center, Republic of Korea, and discussed the relationships between each. Diverse characteristics were observed among many of the traits, but most of the genetic resources (>90%) were either red or pink-fleshed. Korean originated fruits contained intermediate levels of soluble solid content (SSC) while the USA, Russian, Tajikistan, Turkmenistan, Taiwan, and Uruguay originated fruits had generally the highest levels of soluble solids. The citrulline and arginine contents determined using the High Performance Liquid Chromatography (HPLC) method ranged from 6.9 to 52.1 mg/g (average, 27.3 mg/g) and 1.8 to 21.3 mg/g (average, 9.8 mg/g), respectively. The citrulline content determined using the Citrulline Assay Kit ranged from 6.5 to 42.8 mg/g (average, 27.0 mg/g). Resources with high citrulline and arginine levels contained low SSC, whereas red- and pink-colored flesh samples had less citrulline compared to yellow and orange.